Adicción a las redes sociales y su influencia en el rendimiento académico en estudiantes de la unidad educativa Babahoyo - Cedeño Diaz, Karen Rebeca (2025)
This study aims to analyze the relationship between social media addiction and academic performance in the students of Unidad Educativa Babahoyo. The Primary Mental Abilities Test (PMA) was used to measure intellectual quotient and various cognitive factors, and the Internet Addiction Test (IAT) by Kimberly Young was employed to assess the levels of social media addiction. The results indicate a weak and negative correlation between internet addiction levels and students' academic performance. While a significant portion of students displayed a mild or moderate level of addiction, no strong relationships were found that demonstrated a direct negative impact on their academic performance. The findings suggest that other factors, beyond social media addiction, may influence academic performance, opening the door for future research to explore the underlying causes of this phenomenon.